Analisis Dan Perancangan Jaringan Local Area Network Pada Lab Komputer di SMK Negeri 5 Kota Serang - Bayu Prasetya Julandra; Putri Putri; Ali Mabruri (YCMM, 2022)
Currently technology is developing rapidly and has begun to enter into all aspects of the field, one of which is the development of network technology in the field of education. However, not all of these network technology developments have been implemented in SMK Negeri 5 Serang City, so that problems arise in the laboratory environment about how to analyze and utilize network technology to assist the teaching and learning process in the laboratory room. Network technology that will be applied later can assist in sharing data or devices in one laboratory room. Therefore, the author provides a solution by analyzing the need to design a local area network using a star topology. For the design of the local area network, this is only a design of the shape of the room with the number of computers that have been connected to the network. Where the results obtained from this research are in the form of analysis and design of local area networks in the laboratory of SMK Negeri 5 Serang City which can later be implemented further so that they can be applied in assisting the teaching and learning process in the laboratory space of SMK Negeri 5 Serang City